Book of Abstracts: XIII World Congress of the International University Theatre Association AITU-IUTA. University Theatre in the Time of Global Challenges - Naina, Rimantas; Adomaitis, Vincentas; Adomaitienė, Sonata (Vilnius University Proceedings, 2026)
This volume contains the abstracts presented at the XIII World Congress of the International University Theatre Association (AITU-IUTA), held at Vilnius University, Lithuania, on 8–13 July 2026. Under the theme University Theatre in the Time of Global Challenges, the Congress brought together researchers, theatre educators, artists, and students from around the world to explore the role of university theatre in addressing contemporary global issues. The publication presents contributions on war and conflict, climate change, migration, artificial intelligence, social inclusion, theatre pedagogy, and the future of university theatre in higher education and society.